FINANCIAL STATEMENT INTEGRITY : CORPORATE GOVERNANCE AND QUALITY AUDIT EVIDENCE FROM FOOD AND BEVERAGE COMPANIES IN INDONESIA - Charly Marlinda; Hendy Satria; Ranti Utami; Sri Kurnia; Masyitah As Sahara (PENANOMICS: International Journal of Economics, 2022)
The purpose of this study was to examine the effect of corporate governance and audit quality, corporate governance as proxied by institutional ownership, managerial ownership, audit committees, independent commissioners on the integrity of financial statements in manufacturing companies in the food and beverage industry sub-sector. This study uses a quantitative approach whose research object is taken from a sample of manufacturing companies in the food and beverage industry sub-sector as many as 6 companies during the 4-year observation period in order to obtain 24 observation samples. The analytical method used is multiple linear regression analysis with a significant level of 5%. Based on the results of the study, the multiple linear regression analysis equations are: Financial Statement Integrity = 0.239 – 0.070 Institutional Ownership + 5.371 Managerial Ownership – 0.976 Audit Committee + 4.740 Independent Commissioner – 0.379 audit quality + e. The conclusion of the analysis is partial managerial ownership and independent commissioner affect the integrity of financial statements while institutional ownership, audit committee, and audit quality have no effect on the integrity of financial statements, simultaneously institutional ownership, managerial ownership, audit committee, independent commissioners and audit quality have an effect on the integrity of financial statements. managerial ownership and independent commissioners strengthen their relationship with financial statement integrity and institutional ownership, audit committees, and audit quality weaken their relationship with financial statement integrity. The proxy of corporate governance and audit quality on the coefficient of determination shows the percentage of influence of 83.6%, while the rest is influenced by other variables of 16.4%.